Credit Risk Disclosure Compliance And Bank Performance In Nigeria: A Case Study Of Zenith Bank PLC. - Olaoye, F. O.; Ojuolape, T. C. (Archives of Business Research, 2019)
The study examined the influence of credit risk disclosure compliance on bank performance in Nigeria. IFRS 7 state that entity should disclose credit risk in their financial report. Credit risk may affect going concern concept and audit report is silent about it. The specific objective of the study is to ascertain the influence of credit risk disclosure on bank profitability. Linear regression analysis was used to analyse the data collected from financial reports, with the help of SPSS 20.0 version. The study discovered that there is positive relationship between credit risk disclosure and bank profitability. The study therefore recommends that the financial institutions regulators should enforce credit risk disclosure in their financial reports as this will help the stakeholders to make informed investment decision.